The Influence Of Motivation On Customer Satisfaction Concert Music The B-Zone In Jakarta - Ayuni, Trisda; Dewi, Liliana (Politeknik Internasional Bali, 2023)
This research aims to identify how someone finally decides to go to a music concert by looking at an analysis between Motivation and Customer Satisfaction Concert Music The B-Zone in Jakarta. The B-Zone is a world tour concert by South Korean boy group, The Boyz, held in Jakarta. Visitors to The B-Zone Jakarta are the population of this study using quantitative methods and a sample of 100 respondents. The analysis technique for the data obtained was processed using application SPSS version 23. Based on the results of this study on Correlation Test, Motivation and Customer Satisfaction has a value 0.439 or 43,9% which states that X and Y are significant because 0.00 < 0.05 and is positive and correlated. According to research result, Motivation affect Customer Satisfaction. The conclusion of this research, concert music that motivation influences customer satisfaction, this concert shows that someone who comes to see a music concert is motivated to enjoy it and meet their favorite idol.